Characteristics of Health Protocols and Incidence of COVID-19 in Young Doctors Complete Vaccinated - Kristianti, Asti; Indriyana, Sri Q; Fiddiyanti, Ilma (ACTA Medical Health Sciences, 2022)
COVID-19 is a respiratory disease that has currently become a pandemic in the world. West Java is one of the provinces with the most cases of COVID-19 in Indonesia. Health workers including young doctors are a group that has a very high risk of getting infected with COVID- 19. The purpose of this study was to determine the characteristics of health protocols and COVID-19 cases in young doctors at Faculty of Medicine, General Achmad Yani University (FK UNJANI) who were fully vaccinated against COVID-19. This study was designed as a descriptive study with a cross-sectional approach. The characteristics assesses in this study were: age, gender, and a confirmed history of COVID-19. Data was collected in June 2021- September 2022 using google form to fill out a questionnaire. The questionnaire was filled out by 105 eligible respondents. Respondents have received at least 2 doses of the COVID-19 vaccine and are aged between 22-23 years. The characteristics of respondents were 71 females (68.57%) and 33 males (31.43%). A total of 78.1% had confirmed COVID-19 and 21.9% had never been infected. A total of 52,4% respondents had good health protocols and 47.6% had poor health protocols. DOI : 10.35990/amhs.v1n2.p79-87 REFERENCES World Health Organization (WHO). (2020). Health topics: coronavirus. Retrieved April 2021 from https://www.who.int/health-topics/coronavirus Burhan, E., Susanto, A. D., Nasution, S. A., Ginanjar, E., Pitoyo, C. W., Susilo, A., et al. (2020). Pedoman tatalaksana COVID-19 (Edisi ke-3). PDPI, PERKI, PAPDI, PERDATIN, IDAI. Jakarta. Handayani, D., Hadi, D. W., Isbaniah, F., Burhan, E., & Agustin, H. (2020). Penyakit Virus Corona 2019. Jurnal Respirologi Indonesia, 40, 119–284. Badan Nasional Penanggulangan Bencana (BNPB). (2020). Situasi Virus Corona. Retrieved October 2022 from https://www.covid19.go.id/situasi-virus-corona/ Lovato, A., de Filippis, C., & Marioni, G. (2020). Upper airway symptoms in coronavirus disease 2019 (COVID-19). American Journal of Otolaryngology, 10, 24–37. Maskari, Z. A., Blushi, A. A., Khamis, F., Tai, A. A., Salmi, I. A., Harthi, H. A., et al. (2020). Characteristics of health care workers infected with COVID-19: A cross-sectional observational study. International Journal of Infectious Diseases. https://doi.org/10.1016/j.ijid.2020.10.009 Syafruddin, A., Findyartini, A., Budu, Aras, I., Leatemia, L. D., Wiyanto, M., et al. (2020). Pedoman pelaksanaan pendidikan tahap akademik dan profesi program pendidikan dokter dalam masa pandemi. AIPKI. Jakarta. Kristianti, A., Sutrisno, Kumala, Y. Y., Ratwita, W., Irawan, J., Quintina, S., et al. (2021). Pedoman standar pelaksanaan pendidikan tahap profesi FK UNJANI dalam masa pandemi COVID-19. FK UNJANI. Cimahi. Kementerian Kesehatan Republik Indonesia. (2020). Pedoman pencegahan dan pengendalian Coronavirus Disease (COVID-19). Jakarta. Kementerian Kesehatan Republik Indonesia. (2021). Keputusan Menteri Kesehatan No. HK.01.07/MENKES/4638/2021 tentang Petunjuk Teknis Pelaksanaan Vaksinasi dalam Rangka Penanggulangan Pandemi COVID-19. Kementerian Kesehatan Republik Indonesia. (n.d.). Peraturan Menteri Kesehatan RI. Retrieved from https://hukor.kemkes.go.id Kementerian Kesehatan Republik Indonesia. (2020). Keputusan Menteri Kesehatan RI Nomor HK.01.07/MENKES/382/2020 tentang Protokol Kesehatan bagi Masyarakat di Tempat dan Fasilitas Umum dalam Rangka Pencegahan dan Pengendalian COVID-19. Jakarta. Centers for Disease Control and Prevention (CDC). (n.d.). Your guide to mask. Retrieved from https://www.cdc.gov/coronavirus/2019-ncov/prevent-getting-sick/about-face-coverings.html Milani, G. P., Macchi, M., & Mark, A. G. (2021). Vitamin C in the treatment of COVID-19. Nutrients, 13(4), 1172. https://doi.org/10.3390/nu13041172 Ilie, P. C., Stefanescu, S., & Smith, L. (2020). The role of Vitamin D in the prevention of Coronavirus Disease 2019 infection and mortality. Aging Clinical and Experimental Research, 32, 1195–1198. World Health Organization (WHO). (2009). Hand hygiene: Why, how & when?. Geneva. Kementerian Kesehatan Republik Indonesia. (2020). Panduan Cuci Tangan Pakai Sabun. Jakarta. Centers for Disease Control and Prevention (CDC). (2021, May 20). Events and gatherings. Kraemer, M. U. G., et al. (2020). The effect of human mobility and control measures on the COVID-19 epidemic in China. Science, 368, 493–497. Isbaniah, F., Kusumowardhani, D., Sitompul, P. A., Susilo, A., Wihastuti, R., Setyawaty, R., et al. (2021). Pedoman pencegahan dan pengendalian Coronavirus Disease (COVID-19) Revisi Keempat. Retrieved June 12, 2021, from https://infeksiemerging.kemkes.go.id/ Xiong, Y., Zang, X., Sun, D., & Zhu, W. (2020). Clinical and CT characteristics of healthcare workers with COVID-19. Medical Journal, 99(30), 1–7.